Pengaruh Educational dan Economic Empowerment Terhadap New Venture Creation: Peran Moderasi Entrepreneurial Self-Efficacy - Noormalita Primandaru (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The current condition of women in the Bantul Coast has low knowledge, skills, creative attitudes, and aspirations, which results in many women living in poverty. Therefore, women on the coast need to be empowered. Women's empowerment that needs to be done is empowerment in the economic field which is useful for overcoming poverty and education that is useful for developing organizational skills. This study aims to examine the effect of educational empowerment and economic empowerment on new venture creation and entrepreneurial self-efficacy as moderating variables in women on the Bantul coast. The sample in this study are women who are members of the Family Welfare Development (PKK) group in the coastal village of Bantul. The analytical model used is the Partial Least Square (PLS). The results of this study are the first effect of economic empowerment on new venture creation, the second is the effect of educational empowerment on new venture creation, and the third is entrepreneurial self-efficacy moderating the effect of education empowerment and economic empowerment on new venture creation. The managerial implication in this research is support from the government, universities, private institutions, and the community regarding improving the quality of women's HR strategies, such as insight, knowledge, and skills training, improvement, and development of productive economic activities increasing access to economic resources, such as capital. and information technology, strengthen and develop microeconomic institutions, and develop mutually beneficial business partnerships.